CARDIOVASCULAR DISORDERS WITH HYPOTHYROIDISM AND ADIPOKINES - S. Ye. Myasoyedova (Klinicist)
The article describes the mechanisms of development of cardiovascular disorders and dyslipidemia with hypothyroidism. Reference data are presented that are devoted to the study of adipokines content with hypothyroidism and their effect on echocardiographic indicators.